2017
DOI: 10.1371/journal.pone.0172692
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in patients with subsyndromal symptomatic depression and major depressive disorder

Abstract: BackgroundSubsyndromal symptomatic depression (SSD) is a subtype of subthreshold depressive and can lead to significant psychosocial functional impairment. Although the pathogenesis of major depressive disorder (MDD) and SSD still remains poorly understood, a set of studies have found that many same genetic factors play important roles in the etiology of these two disorders. Nowadays, the differential gene expression between MDD and SSD is still unknown. In our previous study, we compared the expression profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Previous study reported that proteins of the STRN family are enriched in dendritic spines and are principally expressed in neurons [53]. STRN had differential expression in peripheral blood among the patients with major depressive disorder, subsyndromal symptomatic depression, and healthy controls [54]. Another significant result is SLC8A1-AS1 in the current study.…”
Section: Discussionsupporting
confidence: 51%
“…Previous study reported that proteins of the STRN family are enriched in dendritic spines and are principally expressed in neurons [53]. STRN had differential expression in peripheral blood among the patients with major depressive disorder, subsyndromal symptomatic depression, and healthy controls [54]. Another significant result is SLC8A1-AS1 in the current study.…”
Section: Discussionsupporting
confidence: 51%
“…Ideally, samples would come from the same subject collected at the same time ( Sullivan et al ., 2006 ; Leday et al ., 2018 ). This would reduce variation in clinical characteristics that could impact expression ( Ciobanu et al ., 2016 ; Yang et al ., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important that there is noticeable variability in the methodology for the quantification of gene expression in studies of psychiatric samples published over the last 2 years. When considering only studies that reported their method of gene expression quantification, the most commonly used method was the comparative 2 -ΔΔCt method, but there were variations in the data normalisation process: use of one reference gene (Amidfar et al, 2017;Bobińska, Gałecka, et al, 2017;Bobińska, Mossakowska-Wójcik, et al, 2017;Liu et al, 2017;Yang et al, 2017;Fries et al, 2017;Gałecka et al, 2017Gałecka et al, , 2018Ghafelehbashi et al, 2017;Hoseth et al, 2017;Hung et al, 2017;Akcan et al, 2018;Sao et al, 2018), relativity to their own endogenous control (Doolin et al, 2017), two reference genes (Roy et al, 2017), and geometric mean of two reference genes (Chau et al, 2018). This source of variability may difficult the interpretation (and comparison) of the results of gene expression studies of psychiatric conditions; moreover, it impedes the realisation of meta-analysis.…”
Section: Discussionmentioning
confidence: 99%